Recent Advances in Capillary Electrochromatography of Proteins and Carbohydrates in the Biopharmaceutical and Biomedical Field. (7th May 2021) - Hajba, L.; Guttman, A.
Abstract: Capillary electrochromatography (CEC) is a powerful hybrid separation technique that combines capillary electrophoresis and capillary chromatography, capable to address the analytical challenges of proteomics and glycomics. The focus of this paper is to review the recent developments in capillary electrochromatography of proteins and carbohydrates. The different column types applied in capillary electrochromatography such as packed bed, open tubular and monoliths are conferred in detail with respective separation examples. A comprehensive comparison is also given listing the mostly utilized coating methods, stationary phase materials and column preparation methods. The choice of porogenic solvent combinations for monolithic column fabrication is thoroughly discussed, paying close attention to the fine tuning options for the separation driving electroosmotic flow. Application examples of CEC in process analytical technology for the biopharmaceutical and biomarker discovery in the biomedical fields are also given.